Two wheels mobile robot control using linear quadratic regulator and pole placement controller - Donny, Anak Ju (2009)
There is various type of controller that able to use in control a balancing of two wheels mobile robot. In term to control the two wheels mobile robot, there are four criteria’s that need to consider. The four criteria’s that control the balancing of two wheels mobile robot are position, speed, angle, and angle rate. From state space equation, two wheels mobile robot is presented using MATLAB application. Linear quadratic regulator (LQR) and Pole place are designed to control the balancing of two wheels mobile robot. Disturbance is applied to angle rate to test the balancing of robot. Simulation on MATLAB application is analyzed and the LQR and Pole placement controller performance are compared to find out the best controller for two wheels mobile robot model.